2021
DOI: 10.3389/fnhum.2021.715212
|View full text |Cite
|
Sign up to set email alerts
|

Dissociating the Impact of Movement Time and Energy Costs on Decision-Making and Action Initiation in Humans

Abstract: Recent theories and data suggest that adapted behavior involves economic computations during which multiple trade-offs between reward value, accuracy requirement, energy expenditure, and elapsing time are solved so as to obtain rewards as soon as possible while spending the least possible amount of energy. However, the relative impact of movement energy and duration costs on perceptual decision-making and movement initiation is poorly understood. Here, we tested 31 healthy subjects on a perceptual decision-mak… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(33 citation statements)
references
References 59 publications
3
30
0
Order By: Relevance
“…Similarly, it makes sense that task-based brain analyses would reveal strong similarities between subjects: given that large-scale brain anatomy is very similar across people (Hagoort, 2019; Sanes et al, 1995), the same brain areas will likely be involved for everyone in a given task. However, variations in performance from one trial or block to the next would logically depend on different mechanisms for different people (Saleri Lunazzi et al, 2021). For example, someone whose attention is captured too strongly by the visual stimuli may show lower RT with lower visual cortex activity and higher motor cortex activity.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, it makes sense that task-based brain analyses would reveal strong similarities between subjects: given that large-scale brain anatomy is very similar across people (Hagoort, 2019; Sanes et al, 1995), the same brain areas will likely be involved for everyone in a given task. However, variations in performance from one trial or block to the next would logically depend on different mechanisms for different people (Saleri Lunazzi et al, 2021). For example, someone whose attention is captured too strongly by the visual stimuli may show lower RT with lower visual cortex activity and higher motor cortex activity.…”
Section: Discussionmentioning
confidence: 99%
“…The decision and motor behaviors of these subjects have been described in three recent publications reporting the effects of the decisional context on movement properties (Thura, 2020) and the effects of the motor context on decision strategies (Reynaud et al, 2020; Saleri Lunazzi et al, 2021). In these reports, subjects' behavioral adjustments are described either within a given trial (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…In the first experiment (Reynaud et al, 2020; Thura, 2020), participants could invest up to 3s in the decision process and had up to 800ms to execute the reaching movement expressing a choice. In the other experiment (Saleri Lunazzi et al, 2021), the decision component of the task was similar but reaching duration was strictly bounded. By analyzing changes of several decision and motor parameters from one trial to the next, we found multiple context-dependent post-decision and post-movement outcome adjustments of both subsequent decision and motor speed-accuracy tradeoffs.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations